Group Investigation Assisted by Media Flip Chart can Improve Science Learning Outcomes and Cooperative Attitudes - Nofita, Ersi; Rusnilawati (LPPM Undiksha, 2022)
Using innovative models and media in the learning process will affect the learning outcomes of elementary school students. This study aims to analyze the use of the group investigation learning model with the help of flipchart media on learning outcomes and cooperative attitudes in fourth-grade elementary school science material. The design of this study was a quasi-experimental design with a non-equivalent control group design. The subject of this research is class IV which consists of 42 students. Samples were taken by random sampling technique. The data in this study were obtained through observation, interviews, documentation, and tests. The data obtained were analyzed using the t-test. Based on the analysis of the questionnaire data, it was found that Sig 0.033 was less than 0.05. Ho was rejected, meaning there was a significant difference in attitude between the control and experimental groups. Based on the learning outcomes test data analysis, Sig 0.00 is less than 0.05. Ho is rejected, which means there are differences in learning outcomes before and after being given the media and model treatment. So, there is an influence of the group investigation model assisted by flipchart media on improving elementary school students' learning outcomes and cooperative attitudes. This research implies that teachers are expected to be able to create a comfortable atmosphere so that students' understanding of experiences will be more honed.